A kind of cast iron sand mold coating and preparation method thereof

By reasonably comparing light magnesium sand powder, heavy magnesium sand powder and zircon powder in cast iron sand coatings, and combining specific combinations of suspension agents, binders and additives, the problem of poor anti-seepage sulfur effect of existing shielded coatings is solved, and a thicker and more stable anti-seepage sulfur coating is achieved, reducing the spheroidization risk and production cost of castings.

CN119407097BActive Publication Date: 2025-04-11HIMILE MECHANICAL SCI & TECH (SHANDONG) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510031059.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing shielded coatings have problems such as thin thickness, poor stability, average effect, and large gas production, resulting in poor spheroidization of castings and casting defects, high production costs and poor stability.

Method used

Cast iron sand coatings consisting of refractory fillers, liquid carriers, suspension agents, binders and additives are used to improve the sulfur absorption activity, refractory properties and adhesion of the coating by reasonably combining light magnesium sand powder, heavy magnesium sand powder and zircon powder, and combined with specific combinations of suspensions, binders and additives.

Benefits of technology

It effectively solves the problems of thin thickness, poor stability, average effect, and large gas production, avoids poor spheroidization and casting defects, reduces production costs, and improves the stability and anti-sulphur effect of castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119407097B_ABST
    Figure CN119407097B_ABST
Patent Text Reader

Abstract

The present invention provides a cast iron sand mold coating and a preparation method thereof, and relates to the field of casting sand mold coating. The cast iron sand mold coating of the present invention is composed of the following raw materials: refractory filler, liquid carrier, suspending agent, binder, and auxiliary agent; the weight percentage dosage of each of the raw materials is: refractory filler 65-70%, liquid carrier 19-25%, suspending agent 2-4%, binder 4.4-5.5%, auxiliary agent 2.4-3%; the refractory filler is composed of magnesia powder, zircon powder, and graphite powder; the magnesia powder is composed of light magnesia powder and heavy magnesia powder. The cast iron sand mold coating of the present invention and the preparation method thereof can effectively solve the problems of thin thickness of anti-sulfurization coating, poor stability of anti-sulfurization coating, general anti-sulfurization effect, and large gas generation in the existing shielding type coating, effectively avoid poor spheroidization and casting defects of castings, reduce production costs, and improve casting stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of casting sand mold coating, in particular to a cast iron sand mold coating and a preparation method thereof. Background Art

[0002] When furan resin sand process is used to produce ball-milled castings, the benzenesulfonic acid in the resin sand curing agent decomposes at high temperature: CH3C6H4SO3H +XO2→YCO2+ZCO+PH2O+QC m H n +SO2↑, producing gas containing sulfur dioxide; sulfur-containing gas entering the casting will cause spherical graphite to become flake graphite, and flake graphite has a splitting effect on the metal matrix, directly leading to a decrease in the tensile strength of the casting, greatly increasing the risk of fracture of the casting under stress conditions. In the prior art, a common method to improve the above-mentioned problem is to apply a layer of coating on the surface of the sand mold to isolate the sulfur-containing gas from invading the casting.

[0003] At present, the commonly used anti-sulfur coatings are mainly divided into the following three types:

[0004] 1. Barrier coating. It has high sintering performance. Under the action of high-temperature molten iron, this type of coating can form a hard and dense sintering shell between the mold and the metal liquid surface, thereby preventing the SO2 gas decomposed by heat in the molding sand from directly contacting the molten iron interface. The material that plays a barrier role in barrier coatings is generally zircon powder, or zircon powder combined with low-refractory materials such as rutile.

[0005] 2. Absorption coating. Generally, some alkaline substances are added to the components of the coating. The addition of alkaline substances can react with the SO2 gas decomposed by heat in the molding sand to generate solid products that remain in the coating, thereby preventing the SO2 gas from directly contacting the iron liquid interface. The materials that play an absorbing role in absorption coatings are generally alkaline materials such as calcium oxide or magnesium oxide.

[0006] 3. Shielding coating (blocking + absorption). Single barrier coating or absorption coating has limited effect on reducing or eliminating the surface sulfurization of ductile iron castings. Shielding coating with both blocking and absorption effects is the most effective way to reduce or eliminate the surface sulfurization of ductile iron castings produced by furan resin sand.

[0007] However, the existing shielding coatings have the problems of thin anti-sulfurization coating thickness, poor stability of the anti-sulfurization coating, general anti-sulfurization effect, and large gas generation, which directly lead to shortcomings such as poor spheroidization of castings, casting defects, high production costs, and poor stability of castings. Therefore, a cast iron sand mold coating and a preparation method thereof are needed to solve the above technical defects. Summary of the invention

[0008] In order to solve the technical problems existing in the prior art, the present invention provides a cast iron sand mold coating and a preparation method thereof, which can effectively solve the problems of thin anti-sulfurization coating thickness, poor stability of anti-sulfurization coating, general anti-sulfurization effect, and large gas evolution in the existing shielding type coating, effectively avoid poor spheroidization and casting defects of castings, reduce production costs, and improve casting stability.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0010] A cast iron sand mold coating, comprising the following raw materials: refractory filler, liquid carrier, suspending agent, binder, and auxiliary agent;

[0011] The weight percentage of each raw material is: refractory filler 65-70%, liquid carrier 19-25%, suspending agent 2-4%, binder 4.4-5.5%, auxiliary agent 2.4-3%;

[0012] The refractory filler is composed of magnesia powder, zircon powder and graphite powder; the magnesia powder is composed of light magnesia powder and heavy magnesia powder;

[0013] The liquid carrier is isopropanol and / or methanol;

[0014] The suspending agent is magnesium aluminum silicate and / or attapulgite;

[0015] The binder is composed of phenolic resin, polyvinyl butyral PVB and silica sol;

[0016] The additives include: white carbon black, polyvinyl alkyl alcohol ether OP-10, and red iron oxide.

[0017] Preferably, in the magnesia powder, the weight ratio of light magnesia powder to heavy magnesia powder is 1:3-10.

[0018] Preferably, in the refractory filler, the purity of the light magnesia powder is ≥99.9wt%; the purity of the heavy magnesia powder is ≥93wt%; more preferably, the mesh number of the heavy magnesia powder is ≥270 mesh.

[0019] The chemical composition and content of zircon powder are: ZrO2>66wt%, SiO2<33wt%, TiO2<0.4wt%, Fe2O3<0.1wt%; more preferably, the particle size specification of the zircon powder is: 95wt% passes through a 320-mesh sieve, and the residue passes through a 260-mesh sieve; refractoriness ≥1550°C; density 4.6-4.71g / cm 3 ; Refractive index 1.93-1.98.

[0020] The purity of the graphite powder is ≥99wt%; more preferably, the mesh number of the graphite powder is ≥325 mesh.

[0021] Preferably, in the liquid carrier, the purity of isobutanol is not less than 99.5wt%; the purity of methanol is not less than 99.5wt%, and does not contain free formaldehyde;

[0022] When the liquid carrier is isopropanol and methanol, the weight ratio of isopropanol to methanol is 1:1-4.

[0023] Preferably, when the suspending agent is magnesium aluminum silicate and attapulgite, the weight ratio of magnesium aluminum silicate to attapulgite is 0.5-2:1.

[0024] More preferably, the fineness specifications of the attapulgite are: 200 mesh sieve pass rate> 90wt%, 24h expansion value in 3g / 100mL solvent ≥96%.

[0025] Preferably, in the binder, the weight ratio of phenolic resin, polyvinyl butyral PVB, and silica sol is 5-20:1:9-35.

[0026] More preferably, the phenolic resin is a thermosetting phenolic resin, with a free phenol content of ≤0.1 wt % and a moisture content of ≤0.5 wt %.

[0027] More preferably, the silica sol has a silicon dioxide content of 15-35 wt %; a pH value of 8.5-10; and a density of 1.15-1.21 g / cm 3 ; Sodium ion content ≤0.02%; average particle size is 10-20nm.

[0028] Preferably, in the cast iron sand mold coating, the weight percentage of each raw material is: zircon powder 10-15%, graphite powder 10-15%, light magnesia powder 5-10%, heavy magnesia powder 30-40%, isopropyl alcohol 5-10%, methanol 10.4-18.3%, magnesium aluminum silicate 1-2%, attapulgite 1-2%, phenolic resin 1.5-2%, polyvinyl butyral 0.1-0.3%, silica sol 2.5-3.5%, white carbon black 0.3-0.6%, polyvinyl alkyl alcohol ether 0.2-0.3%, and red iron oxide 1.5-2.5%.

[0029] A method for preparing the aforementioned cast iron sand mold coating comprises the following steps: preparing a polyvinyl butyral dilution solution and mixing;

[0030] The method for diluting the polyvinyl butyral solution is to uniformly disperse the polyvinyl butyral PVB and a liquid carrier to obtain the polyvinyl butyral diluent;

[0031] The mixing method is to evenly disperse the remaining raw materials and the polyvinyl butyral diluent according to weight percentage to obtain the cast iron sand mold coating.

[0032] Preferably, the content of polyvinyl butyral in the polyvinyl butyral dilution is 10-30wt%.

[0033] More preferably, during the mixing, the dispersion rotation speed is 400-600 rpm.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The cast iron sand mold coating and its preparation method of the present invention select the proportion of each raw material component of the cast iron sand mold coating, especially the reasonable proportion of light magnesia powder, heavy magnesia powder and zircon powder in the refractory filler, and combine the light magnesia powder with high activity and the heavy magnesia powder with high refractoriness, and cooperate with zircon powder to achieve that the coating has both strong sulfur absorption activity and fire resistance and fireproof performance, and reduces gas emission; effectively prevents sand sticking and is easy to form vitrification, further playing a shielding role; effectively avoids the occurrence of poor spheroidization when producing ductile iron by furan resin sand process, improves casting performance and stability, and avoids casting defects; wherein the specific process of sulfur absorption is as follows:

[0036] ;

[0037] At the same time, if Figure 1 As shown, zircon powder has a wide sintering temperature range and high refractoriness, and is easy to sinter in a high temperature environment to form a shielding layer, further preventing sulfur-containing gases from penetrating the coating layer; further, polyvinyl alkyl alcohol ether OP-10 with surfactant function is specifically provided in the coating to reduce the surface tension of the coating while increasing the penetration depth of the coating in the sand, thereby promoting the formation of a thicker anti-sulfur layer; the thickness of the formed coating is 0.2-0.4mm, and the coating has good anti-sulfur stability. Through the isolation and absorption of the coating, the adverse effects of sulfur-containing gases on the surface weight of the casting are effectively eliminated.

[0038] (2) The cast iron sand mold coating of the present invention can improve the surface strength and anti-foaming performance of the cast iron sand mold coating while improving the adhesiveness and film-forming properties of the cast iron sand mold coating by selecting a specific combination of suspending agents, binders, and additives in combination with zircon powder, and can also improve its application performance and film-forming weight by adjusting the viscosity of the cast iron sand mold coating such as thickening. In addition, polyvinyl alkyl alcohol ether OP-10 with a surfactant function is provided to reduce the surface tension of the coating while increasing the penetration depth of the coating in the sand, promote the formation of a thicker anti-sulfur layer, and effectively improve the anti-sulfur effect. The aforementioned technical means cooperate with each other and work synergistically, which can effectively solve the problems of the existing shielding type coating, such as thin anti-sulfurization coating thickness, poor stability of the anti-sulfurization coating, general anti-sulfurization effect, and large gas generation, effectively avoid poor spheroidization of castings and casting defects, reduce production costs, and improve casting stability.

[0039] (3) The coating formed by the cast iron sand mold coating of the present invention has a sulfurization ratio of no more than 2.5%, and there is no sulfurization color difference in the subsequent processing process, which effectively avoids sulfurization and scrapping, and can effectively improve the casting yield.

[0040] (4) The viscosity of the cast iron sand mold coating of the present invention is 15.1-16.9 seconds, the suspension rate is 97.3-98.4% within 2 hours, and the gas evolution value is 30.5-37.5 mL. The cast iron sand mold coating has good stability and is easy to apply and use.

[0041] (5) The raw materials of the cast iron sand mold coating of the present invention are cheap and easily available, which can further reduce the coating cost and casting production cost while ensuring its performance, and is conducive to large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic diagram of the penetration of coating for cast iron sand mold of the present invention.

[0043] Figure 2 This is a photograph of a casting machined to a depth of 2 mm using the cast iron sand mold coating of Example 6.

[0044] Figure 3 for Figure 2 Metallographic microscopic observation picture at the red circle in the middle.

[0045] Figure 4 This is a photograph of a casting machined to a depth of 2 mm using the cast iron sand mold coating of Comparative Example 1.

[0046] Figure 5 for Figure 4 Metallographic microscopic observation picture at the red circle in the middle. DETAILED DESCRIPTION

[0047] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0048] Example 1

[0049] The present embodiment provides a cast iron sand mold coating, which is composed of the following raw materials: a refractory filler, a liquid carrier, a suspending agent, a binder, and an additive.

[0050] Among them, the refractory filler is composed of magnesia powder, zircon powder and graphite powder.

[0051] The magnesia powder is composed of light magnesia powder and heavy magnesia powder, and the weight ratio of the light magnesia powder to the heavy magnesia powder is 1:8.

[0052] The purity of lightweight magnesia powder is 99.9wt% and the density is 3.26g / cm 3 .

[0053] The purity of heavy magnesia powder is 93.5wt% and the density is 3.58g / cm 3 , the mesh number is 270 mesh.

[0054] The chemical composition and content of zircon powder are: ZrO2 content is 66.8wt%, SiO2 content is 32.2wt%, TiO2 content is 0.38wt%, Fe2O3 content is 0.09wt%, and the rest is other impurities; the particle size specification is: 95wt% passes through a 320-mesh sieve, and the remaining part passes through a 260-mesh sieve; the refractoriness is 1950℃; the density is 4.65g / cm 3 ; Refractive index is 1.96.

[0055] The purity of graphite powder is 99.2wt% and the density is 2.2g / cm 3 , the mesh number is 325 meshes.

[0056] The liquid carriers are isopropanol and methanol, and the weight ratio of isopropanol to methanol is 1:1.04.

[0057] The purity of isobutanol is 99.6wt%; the purity of methanol is 99.5wt%, and it does not contain free formaldehyde.

[0058] The suspending agent is magnesium aluminum silicate and attapulgite; the weight ratio of magnesium aluminum silicate to attapulgite is 1:1.

[0059] The fineness specifications of attapulgite are: the pass rate through 200 mesh sieve is 92wt%, and the expansion value (3g± / 100mL solvent, 24h) is 96.5%.

[0060] The adhesive consists of phenolic resin, polyvinyl butyral PVB and silica sol; the weight ratio of the phenolic resin, polyvinyl butyral PVB and silica sol is 20:1:25.

[0061] The phenolic resin is a thermosetting phenolic resin with a free phenol content of 0.06wt% and a moisture content of 0.2wt%.

[0062] The silica content in the silica sol is 25wt%; the pH value is 9; the density is 1.18g / cm 3 ; Sodium ion content is 0.01%; average particle size is 13nm.

[0063] The additives are white carbon black, polyvinyl alkyl alcohol ether OP-10 and red iron oxide.

[0064] Specifically, by weight percentage, the specific amount of each raw material in the cast iron sand mold coating of this embodiment is as follows: zircon powder 10%, graphite powder 15%, light magnesia powder 5%, heavy magnesia powder 40%, isopropyl alcohol 10%, methanol 10.4%, magnesium aluminum silicate 1%, attapulgite 1%, phenolic resin 2%, polyvinyl butyral 0.1%, silica sol 2.5%, white carbon black 0.3%, polyvinyl alkyl alcohol ether 0.2%, and red iron oxide 2.5%.

[0065] This embodiment also provides a method for preparing a cast iron sand mold coating, which is specifically:

[0066] 1. Preparation of polyvinyl butyral dilution

[0067] The polyvinyl butyral (PVB) and part of the methanol in the binder are put into the dispersion cylinder of the dispersant and dispersed evenly to obtain a polyvinyl butyral dilution liquid with a polyvinyl butyral (PVB) content of 10 wt%.

[0068] In this step, since polyvinyl butyral PVB has a high viscosity and is not easy to disperse during the mixing process with other raw materials, in order to ensure uniform dispersion, a polyvinyl butyral dilution liquid with a predetermined concentration needs to be pre-prepared in advance.

[0069] 2. Mix

[0070] According to the weight percentage of the above-mentioned raw materials, the remaining raw materials and the remaining amount of liquid carrier are added into the dispersion tank, the dispersion speed is controlled to 400 rpm, and the dispersion is uniformly prepared to obtain the cast iron sand mold coating.

[0071] The cast iron sand mold coating prepared in this embodiment was tested using a coating cup with a diameter of 6 cm. The viscosity of the cast iron sand mold coating was measured to be 15.1 seconds, the suspension rate was 97.8% within 2 hours, and the gas evolution value was 37.5 mL.

[0072] Example 2

[0073] The present embodiment provides a cast iron sand mold coating, which is composed of the following raw materials: a refractory filler, a liquid carrier, a suspending agent, a binder, and an additive.

[0074] The refractory filler is composed of magnesia powder, zircon powder and graphite powder; the magnesia powder is composed of light magnesia powder and heavy magnesia powder.

[0075] The liquid carriers are isopropanol and methanol.

[0076] The suspending agents are magnesium aluminum silicate and attapulgite.

[0077] The adhesive consists of phenolic resin, polyvinyl butyral PVB and silica sol.

[0078] The additives are white carbon black, polyvinyl alkyl alcohol ether OP-10 and red iron oxide.

[0079] The specific specifications of the above raw materials are the same as those in Example 1 and will not be repeated here.

[0080] Specifically, by weight percentage, the specific amount of each raw material in the cast iron sand mold coating of this embodiment is as follows: zircon powder 11%, graphite powder 14%, light magnesia powder 6%, heavy magnesia powder 38%, isopropyl alcohol 9%, methanol 10.6%, magnesium aluminum silicate 1.8%, attapulgite 1.2%, phenolic resin 1.9%, polyvinyl butyral 0.26%, silica sol 3.3%, white carbon black 0.36%, polyvinyl alkyl alcohol ether 0.28%, and red iron oxide 2.3%.

[0081] The preparation method of the cast iron sand mold coating used in this embodiment is the same as that in Example 1.

[0082] The cast iron sand mold coating prepared in this embodiment was tested using a coating cup with a diameter of 6 cm. The viscosity of the cast iron sand mold coating was measured to be 16.9 seconds, the suspension rate was 98.3% within 2 hours, and the gas evolution value was 36.0 mL.

[0083] Example 3

[0084] The present embodiment provides a cast iron sand mold coating, which is composed of the following raw materials: a refractory filler, a liquid carrier, a suspending agent, a binder, and an additive.

[0085] The refractory filler is composed of magnesia powder, zircon powder and graphite powder; the magnesia powder is composed of light magnesia powder and heavy magnesia powder.

[0086] The liquid carriers are isopropanol and methanol.

[0087] The suspending agents are magnesium aluminum silicate and attapulgite.

[0088] The adhesive consists of phenolic resin, polyvinyl butyral PVB and silica sol.

[0089] The additives are white carbon black, polyvinyl alkyl alcohol ether OP-10 and red iron oxide.

[0090] The specific specifications of the above raw materials are the same as those in Example 1 and will not be repeated here.

[0091] Specifically, by weight percentage, the specific amount of each raw material in the cast iron sand mold coating of this embodiment is as follows: zircon powder 12%, graphite powder 13%, light magnesia powder 7%, heavy magnesia powder 36%, isopropyl alcohol 8%, methanol 13.1%, magnesium aluminum silicate 1.6%, attapulgite 1.4%, phenolic resin 1.8%, polyvinyl butyral 0.22%, silica sol 3.1%, white carbon black 0.42%, polyvinyl alkyl alcohol ether 0.26%, and red iron oxide 2.1%.

[0092] The preparation method of the cast iron sand mold coating used in this embodiment is the same as that in Example 1.

[0093] The cast iron sand mold coating prepared in this embodiment was tested using a coating cup with a diameter of 6 cm. The viscosity of the cast iron sand mold coating was measured to be 16.3 seconds, the suspension rate was 98.1% within 2 hours, and the gas evolution value was 34.5 mL.

[0094] Example 4

[0095] The present embodiment provides a cast iron sand mold coating, which is composed of the following raw materials: a refractory filler, a liquid carrier, a suspending agent, a binder, and an additive.

[0096] The refractory filler is composed of magnesia powder, zircon powder and graphite powder; the magnesia powder is composed of light magnesia powder and heavy magnesia powder.

[0097] The liquid carriers are isopropanol and methanol.

[0098] The suspending agents are magnesium aluminum silicate and attapulgite.

[0099] The adhesive consists of phenolic resin, polyvinyl butyral PVB and silica sol.

[0100] The additives are white carbon black, polyvinyl alkyl alcohol ether OP-10 and red iron oxide.

[0101] The specific specifications of the above raw materials are the same as those in Example 1 and will not be repeated here.

[0102] Specifically, by weight percentage, the specific amount of each raw material in the cast iron sand mold coating of this embodiment is as follows: zircon powder 13%, graphite powder 12%, light magnesia powder 8%, heavy magnesia powder 34%, isopropyl alcohol 7%, methanol 15.6%, magnesium aluminum silicate 1.4%, attapulgite 1.6%, phenolic resin 1.7%, polyvinyl butyral 0.18%, silica sol 2.9%, white carbon black 0.48%, polyvinyl alkyl alcohol ether 0.24%, and red iron oxide 1.9%.

[0103] The preparation method of the cast iron sand mold coating used in this embodiment is the same as that in Example 1.

[0104] The cast iron sand mold coating prepared in this embodiment was tested using a coating cup with a diameter of 6 cm. The viscosity of the cast iron sand mold coating was measured to be 15.8 seconds, the suspension rate was 98.4% within 2 hours, and the gas evolution value was 33.2 mL.

[0105] Example 5

[0106] The present embodiment provides a cast iron sand mold coating, which is composed of the following raw materials: a refractory filler, a liquid carrier, a suspending agent, a binder, and an additive.

[0107] The refractory filler is composed of magnesia powder, zircon powder and graphite powder; the magnesia powder is composed of light magnesia powder and heavy magnesia powder.

[0108] The liquid carriers are isopropanol and methanol.

[0109] The suspending agents are magnesium aluminum silicate and attapulgite.

[0110] The adhesive consists of phenolic resin, polyvinyl butyral PVB and silica sol.

[0111] The additives are white carbon black, polyvinyl alkyl alcohol ether OP-10 and red iron oxide.

[0112] The specific specifications of the above raw materials are the same as those in Example 1 and will not be repeated here.

[0113] Specifically, by weight percentage, the specific amount of each raw material in the cast iron sand mold coating of this embodiment is as follows: zircon powder 14%, graphite powder 11%, light magnesia powder 9%, heavy magnesia powder 32%, isopropyl alcohol 6%, methanol 18.1%, magnesium aluminum silicate 1.2%, attapulgite 1.8%, phenolic resin 1.6%, polyvinyl butyral 0.14%, silica sol 2.7%, white carbon black 0.54%, polyvinyl alkyl alcohol ether 0.22%, and red iron oxide 1.7%.

[0114] The preparation method of the cast iron sand mold coating used in this embodiment is the same as that in Example 1.

[0115] The cast iron sand mold coating prepared in this embodiment was tested using a coating cup with a diameter of 6 cm. The viscosity of the cast iron sand mold coating was measured to be 15.1 seconds, the suspension rate was 97.9% within 2 hours, and the gas evolution value was 31.5 mL.

[0116] Example 6

[0117] The present embodiment provides a cast iron sand mold coating, which is composed of the following raw materials: a refractory filler, a liquid carrier, a suspending agent, a binder, and an additive.

[0118] The refractory filler is composed of magnesia powder, zircon powder and graphite powder; the magnesia powder is composed of light magnesia powder and heavy magnesia powder.

[0119] The liquid carriers are isopropanol and methanol.

[0120] The suspending agents are magnesium aluminum silicate and attapulgite.

[0121] The adhesive consists of phenolic resin, polyvinyl butyral PVB and silica sol.

[0122] The additives are white carbon black, polyvinyl alkyl alcohol ether OP-10 and red iron oxide.

[0123] The specific specifications of the above raw materials are the same as those in Example 1 and will not be repeated here.

[0124] Specifically, by weight percentage, the specific amount of each raw material in the cast iron sand mold coating of this embodiment is as follows: zircon powder 15%, graphite powder 10%, light magnesia powder 10%, heavy magnesia powder 30%, isopropyl alcohol 5%, methanol 18.3%, magnesium aluminum silicate 2%, attapulgite 2%, phenolic resin 1.5%, polyvinyl butyral 0.3%, silica sol 3.5%, white carbon black 0.6%, polyvinyl alkyl alcohol ether 0.3%, and red iron oxide 1.5%.

[0125] The preparation method of the cast iron sand mold coating used in this embodiment is the same as that in Example 1.

[0126] The cast iron sand mold coating prepared in this embodiment was tested using a coating cup with a diameter of 6 cm. The viscosity of the cast iron sand mold coating was measured to be 16.5 seconds, the suspension rate was 97.3% within 2 hours, and the gas evolution value was 30.5 mL.

[0127] Comparative Example 1

[0128] The technical solution of Example 6 is adopted, except that light magnesia powder is not used in the magnesia powder, and heavy magnesia powder is used to supplement the added percentage of light magnesia powder (that is, the amount of heavy magnesia powder is 40wt%).

[0129] The cast iron sand mold coating prepared in this embodiment was tested using a coating cup with a diameter of 6 cm. The viscosity of the cast iron sand mold coating was measured to be 16.3 seconds, the suspension rate was 98.1% within 2 hours, and the gas evolution value was 29.3 mL.

[0130] Comparative Example 2

[0131] The technical solution of Example 1 is adopted, except that light magnesia powder is not used in the magnesia powder, and heavy magnesia powder is used to supplement the added percentage of light magnesia powder (that is, the amount of heavy magnesia powder is 45wt%).

[0132] The cast iron sand mold coating prepared in this embodiment was tested using a coating cup with a diameter of 6 cm. The viscosity of the cast iron sand mold coating was measured to be 14.2 seconds, the suspension rate was 96.9% within 2 hours, and the gas evolution value was 31.1 mL.

[0133] The cast iron sand mold coatings of Examples 1-6 and Comparative Examples 1-2 were respectively used to brush the sand molds, and the molten iron was poured with the same package, and it was ensured that only the cast iron sand mold coatings used were single variables; after processing the same positions of the prepared castings to the same depth (2mm), the castings were observed at a depth of 2mm to see whether there was a sulfurization color difference, so as to evaluate the anti-sulfurization effect of the coating. Among them, if no sulfurization color difference was observed, it means that the anti-sulfurization effect of the cast iron sand mold coating is good; if no sulfurization color difference was observed, it means that the anti-sulfurization effect of the cast iron sand mold coating is relatively poor. The specific results are shown in the following table:

[0134]

[0135] Furthermore, after the castings were processed using the cast iron sand mold coatings of Example 6 and Comparative Example 1, metallographic microscopic observations were performed at a depth of 2 mm. Figure 2 As shown, there is no sulfurization color difference at a depth of 2 mm in the casting of Example 6, and no non-spheroidization color difference occurs; Figure 2 Metallographic microscopic observation (the red circle in the middle) was performed. Figure 3 As shown, it can be seen that the metallographic structure is spherical graphite. Figure 4 As shown in the figure, there is an obvious large area of ​​sulfurization color difference at a depth of 2mm in the casting of Comparative Example 1, which is analyzed as poor spheroidization color difference; Figure 4 Metallographic microscopic observation (the red circle in the middle) was performed. Figure 5 As shown, it can be seen that the metallographic structure is all flake graphite.

[0136] It can be seen that the cast iron sand mold coating and the preparation method thereof of the present invention select the proportion of each raw material component of the cast iron sand mold coating, especially the reasonable proportion of light magnesia powder, heavy magnesia powder and zircon powder in the refractory filler, and combine the light magnesia powder with high activity with the heavy magnesia powder with high refractoriness, and cooperate with zircon powder to achieve that the coating has both strong sulfur absorption activity and refractory and fireproof properties, and reduces gas emission; effectively prevents sand sticking and is easy to form vitrification, further playing a shielding role; effectively avoids the occurrence of poor spheroidization when producing ductile iron by the furan resin sand process, improves casting performance and stability, and avoids casting defects; at the same time, zircon powder has a wider sintering temperature range and higher refractoriness, and is easy to sinter to form a shielding layer in a high temperature environment, further preventing sulfur-containing gas from penetrating the coating layer. The cast iron sand mold coating is combined with zircon powder by selecting a specific combination of suspending agent, binder, and auxiliary agent, which can further improve the surface strength and anti-foaming performance of the cast iron sand mold coating, improve the adhesiveness and film-forming property of the cast iron sand mold coating, and improve its application performance and film-forming weight by adjusting the viscosity of the cast iron sand mold coating such as thickening; and polyvinyl alkyl alcohol ether OP-10 with surfactant function is arranged in combination, which can reduce the surface tension of the coating and increase the penetration depth of the coating in the sand, promote the formation of a thicker anti-sulfur layer, and effectively improve the anti-sulfur effect; the aforementioned technical means cooperate with each other and work synergistically, which can effectively solve the problems of thin anti-sulfurization coating thickness, poor stability of anti-sulfurization coating, general anti-sulfurization effect, and large gas generation in the existing shielding type coating, effectively avoid poor spheroidization of castings and casting defects, reduce production costs, and improve casting stability.

[0137] Unless otherwise specified, all percentages used in the present invention are by weight.

[0138] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A cast iron sand mold coating, characterized in that: It is composed of the following raw materials: refractory filler, liquid carrier, suspending agent, binder, and additive; The refractory filler is composed of magnesia powder, zircon powder and graphite powder; the magnesia powder is composed of light magnesia powder and heavy magnesia powder; The liquid carrier is isopropanol and methanol; The suspending agent is magnesium aluminum silicate and attapulgite; The binder is composed of phenolic resin, polyvinyl butyral PVB and silica sol; The auxiliary agents are white carbon black, polyvinyl alkyl alcohol ether OP-10 and red iron oxide; In the cast iron sand mold coating, the weight percentage of each raw material is: zircon powder 10-15%, graphite powder 10-15%, light magnesia powder 5-10%, heavy magnesia powder 30-40%, isopropyl alcohol 5-10%, methanol 10.4-18.3%, magnesium aluminum silicate 1-2%, attapulgite 1-2%, phenolic resin 1.5-2%, polyvinyl butyral PVB 0.1-0.3%, silica sol 2.5-3.5%, white carbon black 0.3-0.6%, polyvinyl alkyl alcohol ether OP-10 0.2-0.3%, and red iron oxide 1.5-2.5%.

2. The cast iron sand mold coating according to claim 1, characterized in that: In the refractory filler, the purity of the light magnesia powder is ≥99.9wt%; the purity of the heavy magnesia powder is ≥93wt%; The chemical composition and content of zircon powder are: ZrO2>66wt%, SiO2<33wt%, TiO2<0.4wt%, Fe2O3<0.1wt%; The purity of graphite powder is ≥99wt%.

3. A method for preparing a cast iron sand mold coating as claimed in claim 1 or 2, characterized in that: The method comprises the following steps: preparing a polyvinyl butyral dilution solution and mixing it; The method for diluting the polyvinyl butyral solution is to uniformly disperse the polyvinyl butyral PVB and a liquid carrier to obtain the polyvinyl butyral diluent; The mixing method is to evenly disperse the remaining raw materials and the polyvinyl butyral diluent according to weight percentage to obtain the cast iron sand mold coating.

4. The method for preparing the cast iron sand mold coating according to claim 3, wherein: In the polyvinyl butyral dilution solution, the content of polyvinyl butyral PVB is 10-30wt%.

Citation Information

Patent Citations

  • Environment-friendly alcohol-based coating for sand mold casting

    CN104550679A

  • Coating for casting of wind power generator ductile iron hub and preparation method and application thereof

    CN110465622A